Case report: Clinicopathological characteristics of SASH1 mutation-related dyschromatosis: a rethinking of the classification of dyschromatosis - Wang, Tingmei; Li, Dong; Deng, Yunhua (Frontiers in Genetics, 2025)
Dyschromatosis, a group of pigmentary dermatoses, accompany both hyper- and hypo-pigmentation, including dyschromatosis symmetrica hereditaria (DSH), dyschromatosis universalis hereditaria (DUH), and familial progressive hyper- and hypo-pigmentation (FPHH). A peculiar phenotype of dyschromatosis presented as multiple lentigines and hypopigmentation with various sizes and shapes was found to be associated with SASH1 mutations and has recently been reported frequently. The current study evaluated the clinical manifestation, pathological pattern, and genetic basis of dyschromatosis in a five-generation family. This research also presents a case study of a sporadic patient with dyschromatosis caused by SASH1 mutations and shows different clinicopathological characteristics form DSH, DUH and FPHH. SASH1 (SAM and SH3 Domain Containing 1) gene, located on chromosome 6q24.3, encodes a tumor suppressor protein involved in cell signaling, migration, and adhesion. Additionally, the SASH1 mutations could also lead to another pigmentary phenotype: multiple lentigines. High consistency in clinicopathological features and genetic basis in these two SASH1-related pigmentary disorders suggests that SASH1 mutations cause multiple lentigines and dyschromatosis which might belong to a disease spectrum. Overall, it is expected the current study results could help enhance a more comprehensive understanding of SASH1-related pigmentary dermatoses.